"TSA KO KASI", Refashioning the Spaza Shop through social and cultural agency in Katlehong - Mashiloane, Modiehi (My University, 2023)
This dissertation report is an investigation of the economic landscapes on the scope of social and cultural agencies of spaza microenterprises and spatial dynamics of communities in Katlehong township. The report outlines research for a new social infrastructure design proposal, that addresses social and cultural agencies aimed at the disparity of township economic sectors and how they can be improved. The primary objective is the deconstruction of predetermined concepts of spaza shops as a survival mechanism rather than an opportunity that bridges the gap of innovation and acts as an integral component for communities in the township. Informality has frequently been cast in the shadows of the formal retail landscape in the economic district, owing to its evolving perception as subordinates to organizations not constituted in the grey economy (Ohnsorge & Shu, 2021). The grey economy is unregulated and unsupervised informal businesses that are not taxed by the government (Bosanquet & Proppe, 1991). Spaza shops in the informal catalogue are a prime example of globally shadowed micro-enterprises that have numerous benefits to society. They form an integral component in township areas because of their diverse value to communities, including their supply of food security, community integration, employment, and artistic demonstration (Lesley, 2021). Research is proposed for the design of a social and civic infrastructure center in Katlehong. An architectural intervention interlinking identified programme that would sustain growth in the township is to be developed. The infrastructure proposes a permanent and temporary platform for informal markets to be established on a basis that relates to the cultural and social identities of the township. Social aspects derived from the spaza shop culture are explored for entertainment and the exchange of community values.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, 2023